The stylistics of dream-pop songs: Cigarette After Sex’s lyrics analysis - Nency Asgita; Nur Utami Sari’at Kurniati; Dyah Kristyowati (Universitas Pakuan, 2026)
This study aims to analyze the forms and functions of hyperbole found in the lyrics of Cigarettes After Sex songs. The study uses a qualitative method. The data were collected using observation and note-taking techniques, and analyzed using Claridge’s (2011) theory of hyperbole forms and Cano Mora’s (2006) theory of hyperbole functions. The primary data were taken from seven Cigarettes After Sex’s songs: apocalypse, Nothing’s Gonna Hurt You Baby, Sweet, affection, K., Opera House, and Bubblegum. The analysis found 25 hyperbolic expression, with clausal hyperbole as the most dominant form (12 data). Emphasis was the most common function 911 data). Hyperboles are used to express deep emotions such as love, longing, and sadness in the lyrics. This research contributes to the understanding of stylistic in music, particularly in the use of hyperbole to convey emotional messages.